Exploring the Demographic, Clinical, and Molecular Characteristics of Young Women Diagnosed with Ovarian Cancer: A Retrospective Analysis at Luramay General - Diah Rahmayani; Suci Amalia (International Journal on ObGyn and Health Sciences, 2023)
This research delves into the nuanced characteristics of young ovarian cancer patients at Luramay General, offering a comprehensive analysis that illuminates the demographic, clinical, and molecular dimensions of the disease within this specific demographic. A retrospective observational study design was employed, utilizing extensive medical records to systematically examine a cohort of young women diagnosed with ovarian cancer. Key findings include a diverse age distribution, emphasizing the prevalence of cases in women in their reproductive years. Histological analysis revealed a spectrum of tumor subtypes, with a notable predominance of aggressive histologies such as high-grade serous carcinoma. Genetic predisposition, particularly mutations in BRCA1 and BRCA2 genes, was identified, prompting the integration of genetic counseling into clinical care. Challenges associated with late-stage diagnoses underscored the imperative for enhanced early detection strategies. Fertility preservation considerations within treatment modalities highlighted the importance of addressing reproductive concerns in this demographic. The implications of these findings extend to clinical practice, advocating for tailored treatment approaches and heightened awareness, while also informing avenues for further research into molecular profiling, targeted therapies, long-term survivorship experiences, risk stratification models, and community education programs. This research contributes to a more nuanced understanding of ovarian cancer in young women, paving the way for personalized care strategies and advancements in research that can ultimately enhance outcomes for this vulnerable patient population.